Inheritance of resistance to dry root rot in clusterbean - K.R. SOLANKI, SATISH LODHA and (Indian Phytopathology, 2002)
Inheritance of resistance to dry root rot caused by Macrophomina phaseolina in clusterbean was studied. Scaling test revealed the presence of epistasis in R x Rand S x S crosses and appropriateness of additive dominance model for R x S cross. In gene effect studies, additive, additive x additive and dominance x dominance were more pronounced in R x S cross. Low value cf heritability (37.8%) indicated significant role of environmental conditions in the expression of this trail.